COUNSELING AND INTRODUCTION OF RELIGIOUS VALUES AND BELIEFS OF DAYAK NGAJU COMMUNITY IN TUMBANG LITING VILLAGE, KATINGAN HILIR DISTRICT, KATINGAN REGENCY: PENYULUHAN DAN PENGENALAN NILAI-NILAI RELIGI DAN KEPERCAYAAN MASYARAKAT DAYAK NGAJU DI DESA TUMBANG LITING KECAMATAN KATINGAN HILIR KABUPATEN KATINGAN - Ahmad Satria; Wigo Rianor; Mahpidi Yanti; Mesri Uli Panjaitan; Sakman Sakman; Dotrimensi Dotrimensi (Yayasan Education and Social Center, 2021)
This study was conducted to analyze how the Religious Values and Beliefs of the Ngaju Dayak Community in Tumbang Liting Village, Katingan Hilir District, Katingan Regency, Central Kalimantan Province. The method used in this research is descriptive qualitative. Data sources are primary data and secondary data. The primary data sources in this study were the Village Head/Village Secretary, Religious Leaders, and the local community. Secondary data is data directly collected by researchers as a support from the first source. It can also be said that data is arranged in the form of documents. Secondary data is also data obtained indirectly through intermediary media (obtained and recorded by others). Books, Journals, Internet to find valid data. The data collection procedure uses observation, interviews, and documentation while the data analysis includes: Data Collection (Data Collection), Data Reduction (Data Reduction), Data Display (Data Presentation) and Conclusion Drawing (Withdrawal of Conclusions). Based on the results of this study, it shows that the system of religion and belief in Tumbang Liting Village is still very strong and maintained until now. There are 3 religions in Tumbang Liting Village, namely Islam, Christianity, Hindu Kaharingan. For those who are Muslim, the worship system is joined at the Ainul Yaqin Mosque ± 4 KM. Christianity consists of two congregations, namely the Kalawa Church and the Katunen Church. Hinduism in the Temple (Balai). The Islamic death ritual ceremony joins the Kasongan Ainul Yaqin Mosque, the Christian death ceremony includes a 3 night waiting service for the body, burial, and a consolation service. Hindu Kaharingan The death ceremony is carried out for 3 days, the ritual activities, the activities of taking and transferring the bones, then transferred to sandung for 7 days. The attitude of tolerance in Tumbang Liting is very good and mutual respect, respect, if there is a mutual cooperation activity in the community, this is hereby maintained, even though we are now in the modern Technology Age